Plant transposable elements: methods and protocols - Peterson, Thomas, Ed (Methods in molecular biology, 2013)
"Transposable elements have played a major role in shaping plant genome structure and gene expression. Transposons not only drive sequence expansion, induce mutations and generate chromosome rearrangements, they also help to shape the epigenetic topology of the eukaryotic genome. In Plant Transposable Elements: Methods and Protocols, expert researchers in the field detail many of the methods which are now commonly used to study transposons. These methods include computational approaches to study the ancient transposon remnants that comprise the bulk of plant genomes, as well as laboratory techniques to identify recent and ongoing transposition events." --